2022
DOI: 10.15282/jgi.5.2.2022.7103
|View full text |Cite
|
Sign up to set email alerts
|

Internal Corporate Governance Mechanism: A Review

Abstract: Corporate governance (CG) is a comprehensive term that incorporates many distinct facets. Because of numerous financial scandals, public knowledge of CG has increased significantly, particularly in emerging countries like Malaysia. The effectiveness of organizations' adherence with CG legislation and standards is still in question, resulting in numerous incidents of accounting fraud. Furthermore, both internally and externally, company performance is contingent on the effectiveness of Corporate Governance proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…The direct effect occurs without any mediation on remuneration disclosure. In this situation, it is concluded that board structure has a direct effect on firm value which suggest that the board structure itself has the monitoring role as a decision-maker in reducing agency cost thus directly impacting firm value (Wahab, Sapuan, & Abdinazarovich, 2022;Sulong & Nor, 2008). Overall, the mediation analysis reported that the remuneration disclosure does not mediate the relationship between CGM and firm value.…”
Section: Discussion On Disclosure That Mediates the Relationship Betw...mentioning
confidence: 83%
“…The direct effect occurs without any mediation on remuneration disclosure. In this situation, it is concluded that board structure has a direct effect on firm value which suggest that the board structure itself has the monitoring role as a decision-maker in reducing agency cost thus directly impacting firm value (Wahab, Sapuan, & Abdinazarovich, 2022;Sulong & Nor, 2008). Overall, the mediation analysis reported that the remuneration disclosure does not mediate the relationship between CGM and firm value.…”
Section: Discussion On Disclosure That Mediates the Relationship Betw...mentioning
confidence: 83%